Analisis Kemampuan Pemecahan Masalah Matematis Siswa Materi Keliling dan Luas Bangun Datar - Luluk Zakiatus Sholikhah; Heny Oktaviana; Lovika Ardana Riswari (Universitas Muhammadiyah Kuningan, 2023)
This study aims to analyze the math problem solving skills of fourth grade students at SDN 1 Gunung Panti. The method used is Descriptive Qualitative which aims to describe the math problem solving skills of fourth grade elementary school students related to word problems about the area and circumference of flat shapes. The population of this study consisted of 15 fourth grade students at SDN 1 Gunung Panti. The research subjects consisted of 3 students who were selected purposively from the population. Research data was collected through documentation in the form of student answers. The results of the analysis show that there are differences in mathematical abilities between these students. Outstanding students were able to solve all the questions well. Students with moderate achievement show sufficient ability, although there are some errors. Low achieving students still have difficulty in solving word problems about the perimeter and area of ​​flat shapes. Therefore, some students still need guidance from researchers in solving math problems related to the circumference and area of ​​flat shapes.